Consideration on the Regulated Quantity of Preparation for Accidents by Risk Assessment - Ahn, Gwangjae; Kim, Jungwook; Lee, Keunwon; Jung, Seungho (Korean Chemical Engineering Research, 2022)
− In the Chemicals Control Act, a system was implemented to unify off-site risk assessment and risk management plan into the prevention and management system for chemical accidents. Among the hazardous chemicals which have been covered in system, the accident preparation substances are designated as chemical substances that are likely to occur and of which damage scale are likely to be large in the event of chemical accidents. In this study, risks were compared by selecting accident preparation substances with similar regulated quantities. In addition, risk assessment studies were conducted applying the accident scenarios. Four types of materials such as ammonia, hydrogen chloride, carbon disulfide and benzene were selected for the study, and risks were finally analyzed using Safeti 8.0, a quantitative risk assessment program by DNV. As a result, some materials are identified to have high risks comparing to other substances having similar regulated quantities.
Keywords: Accident preparation substances; Regulated quantity; Risk assessment; SAFETI